الموارد الطبيعية الناضبة وأثرها على النمو الاقتصادي: دراسة حالة البترول في الجزائر - أنيسة, بن رمضان; .بلمقدم, مصطفى (Recherches économiques et managériales, 2014)
يعد موضوع اقتصاديات الموارد الطبيعية الناضبة أحد القضايا الأساسية التي أخذت اهتمام الاقتصاديين والدول الغنية بها خاصة في الآونة الأخيرة، وتتم دراستها في إطار قسمين رئيسيين بحيث يهتم القسم الأول بدورها في عملية النمو الاقتصادي في إطار نظرية لعنة الموارد، أما الثاني فيهتم بكيفية تخصيصها. ونهدف في مقالنا هذا إلى توضيح أثر استخدام البترول وعوائده على النمو الاقتصادي في الجزائر، وقد توصلنا إلى أن تزايد معدل استخدام البترول وعوائده ذو أثر سلبي وذلك من خلال الحد من نمو القطاعات الإستراتيجية، حيث أن الثراء الناتج هو ظاهري فقط يتمثل في نمو المؤشرات الاقتصادية الكلية، وبالتالي فإن الجزائر تعاني من لعنة الموارد. الكلمات المفتاح: الموارد الطبيعية الناضبة، النمو الاقتصادي، لعنة الموارد، نموذج Stiglitz، التكامل المتزامن، نموذج تصحيح الخطأ. Abstract The economics of natural resources depleted is fundamental issues took the attention of economists and the rich countries to these resources, especiall in recent times. Exhaustible resources are study in the context of two major parts so intersted in the first part on its role in the processus of economic growth under the theory of the resource curse, and the second interested in how to allocate it. The aim of our article is illustrating the impact of the use of oil and its returns on economic growth in Algeria. We found that the superfat rate of use of oil and its returns have a negative effect through the reduction of the growth of strategic sectors since the rich output is superficial only on the growth of macroeconomic indicators. So Algeria suffers from the curse of resources.   Key words : exhaustible resources, economic growth, resource curse, model of Stiglitz, cointegration, error correction model.